Enhanced Fluorescence for Bioassembly by Environment‐Switching Doping of Metal Ions. (7th January 2020) - Tao, Kai; Chen, Yu; Orr, Asuka A.; Tian, Zhen; Makam, Pandeeswar; Gilead, Sharon; Si, Mingsu; Rencus‐Lazar, Sigal; Qu, Songnan; Zhang, Mingjun; Tamamis, Phanourios; Gazit, Ehud
Abstract: The self‐assembly of cyclodipeptides composed of natural aromatic amino acids into supramolecular structures of diverse morphologies with intrinsic emissions in the visible light region is demonstrated. The assembly process can be halted at the initial oligomerization by coordination with zinc ions, with the most prominent effect observed for cyclo‐dihistidine (cyclo‐HH). This process is mediated by attracting and pulling of the metal ions from the solvent into the peptide environment, rather than by direct interaction in the solvent as commonly accepted, thus forming an "environment‐switching" doping mechanism. The doping induces a change of cyclo‐HH molecular configurations and leads to the formation of pseudo "core/shell" clusters, comprising peptides and zinc ions organized in ordered conformations partially surrounded by relatively amorphous layers, thus significantly enhancing the emissions and allowing the application of the assemblies for ecofriendly color‐converted light emitting diodes. These findings shed light into the very initial coordination procedure and elucidate an alternative mechanism of metal ions doping on biomolecules, thus presenting a promising avenue for integration of the bioorganic world and the optoelectronic field. Abstract : The self‐assembly of aromatic cyclodipeptides can be controlled at the initial oligomerization by coordination with zinc ions, mediated by attraction and pulling of the metal ions from the solvent into the peptide‐rich environment. This "environment‐switching" doping induces configurational changes of the peptides and leads to the formation of pseudo "core/shell" clusters, significantly enhancing the emission of the assemblies in the visible light region.